End Times and Architectural Style on the Christian Campus - Rachel Engler (Footprint)
This paper examines the idea of architectural style on evangelical Christian campuses built during the Cold War, a period during which religious cosmologies came into contact with the prospect of nuclear disaster, allowing for a temporary alliance between secular and religious visions of the end of human history. In this context of Cold War-era end-of-the-world thinking, and in relation to the biblical anticipation of the apocalypse, I consider the contrasting choices of so-called futuristic and neo-vernacular idioms in the building projects of television evangelists. What does it mean to revive styles of the past, or to build in a mode oriented toward the future, when the end of history is imminent? Design undertaken within the framework of assumed apocalyptic narratives troubles notions of permanence and durability—historically vital terms for thinking about building. The paper takes two primary case studies: Robertson’s Regent University in Virginia Beach, which hosts the Christian Broadcasting Network and was built in a “Jeffersonian” vernacular; and Oral Roberts’s Tulsa university, unique at the time for its gilded modernism.